A Frog Peptide Ameliorates Skin Photoaging Through Scavenging Reactive Oxygen Species - Feng, Guizhu; Wei, Lin; Che, Helong; Shen, Yan; Yang, Jun; Mi, Kai; Liu, Jin; Wu, Jing; Yang, Hailong; Mu, Lixian (Frontiers in Pharmacology, 2022)
Although many bioactive peptides have been identified from the frog skins, their protective effects and the molecular mechanisms against skin photodamage are still poorly understood. In this study, a novel 20-residue peptide (antioxidin-NV, GWANTLKNVAGGLCKMTGAA) was characterized from the skin of plateau frog Nanorana ventripunctata. Antioxidin-NV obviously decreased skin erythema, thickness and wrinkle formation induced by Ultraviolet (UV) B exposure in hairless mice. In UVB-irradiated keratinocytes (HaCat cells) and hairless mice, it effectively inhibited DNA damage through reducing p-Histone H2A.X (γH2AX) expression, alleviated cell apoptosis by decreasing the expression of apoptosis-specific protein (cleaved caspase 3), and reduced interleukin-6 (IL-6) production via blocking UVB-activated Toll-like receptor 4 (TLR4)/p38/JNK/NF-κB signaling. In UVB-irradiated fibroblasts (HSF cells) and hairless mice, it effectively restored fibroblast proliferation, and rescued collagen (especially type I collagen) production by restoring transforming growth factor-β1 (TGF-β1)/Smad2 signaling. We found that antioxidin-NV directly and rapidly scavenged intracellular and mitochondrial ROS in HaCat cells upon UVB irradiation, and quickly eliminated the artificial free radicals, 2, 2’-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS+). Taken together, antioxidin-NV directly and rapidly scavenged excessive ROS upon UVB irradiation, subsequently alleviated UVB-induced DNA damage, cell apoptosis, and inflammatory response, thus protecting against UVB-induced skin photoaging. These properties makes antioxidin-NV an excellent candidate for the development of novel anti-photoaging agent.